Effects of bilateral stimulation of the subthalamic nucleus in Parkinson's disease with and without REM sleep behaviour disorder. Issue 12 (17th August 2019) - Bargiotas, Panagiotis; Debove, Ines; Bargiotas, Ioannis; Lachenmayer, Martin Lenard; Ntafouli, Maria; Vayatis, Nicolas; Schüpbach, Michael WM; Krack, Paul; Bassetti, Claudio L
Abstract : Background: Although rapid eye movement sleep behaviour disorder (RBD) in Parkinson's disease (PD) is associated with increased non-motor symptoms, its impact on the deep brain stimulation (DBS) outcome remains unclear. This is the first study to compare the post-DBS outcome between PD patients with RBD (PD-RBD+) and without (PD-RBD-). Methods: We analysed data from PD patients who were treated with bilateral DBS in the nucleus subthalamicus. Assessments included night-polysomnography (only pre-DBS), and motor and non-motor assessments pre-DBS and post-DBS. Results: Among 50 PD patients (29 males, mean age 62.5 years, 11.8 mean PD years), 24 (48%) had RBD. Pre-DBS, the two groups were equal in respect to sociodemographic features, disease duration and PD medications. A multivariate analysis showed that the clinical profile linked to motor, non-motor and quality of life features differed significantly between PD patients with and without RBD. The most discriminative elements were Unified Parkinson's Disease Rating Scale (UPDRS)-III, apathy and depression scores. Post-DBS, UPDRS-III, Epworth sleepiness scale and PD questionnaire improved significantly in both groups. UPDRS-II scores significantly improved in the PD-RBD+ group (−45%) but remained unchanged in the PD-RBD- group (−14%). The depression score improved significantly in the PD-RBD+ (−34%) and remained unchanged in the PD-RBD- group. The apathy score remained unchanged in the PD-RBD+ group but increased significantly in the PD-RBD- group (+33%). Conclusion: While pre-DBS, PD patients with and without RBD showed different clinical profiles, post-DBS, the clinical profiles were comparable between the two groups. In respect to depressive symptoms, apathy and activities of daily living, PD-RBD+ patients show favourable post-DBS outcome. These findings highlight the importance of RBD assessment prior to DBS surgery.